Large Cluster of Neisseria meningitidis Urethritis in Columbus, Ohio, 2015 - Bazan, Jose A.; Turner, Abigail Norris; Kirkcaldy, Robert D.; Retchless, Adam C.; Kretz, Cecilia B.; Briere, Elizabeth; Tzeng, Yih-Ling; Stephens, David S.; Maierhofer, Courtney; Del Rio, Carlos; Abrams, A. Jeanine; Trees, David L.; et al. (Clinical infectious diseases, 2017)
Background. Neisseria meningitidis (Nm) is a Gram-negative diplococcus that normally colonizes the nasopharynx and rarely infects the urogenital tract. On Gram stain of urethral exudates, Nm can be misidentified as the more common sexually transmitted pathogen Neisseria gonorrhoeae. Methods. In response to a large increase in cases of Nm urethritis identified among men presenting for screening at a sexually transmitted disease clinic in Columbus, Ohio, we investigated the epidemiologic characteristics of men with Nm urethritis and the molecular and phylogenetic characteristics of their Nm isolates. The study was conducted between 1 January and 18 November 2015. Results. Seventy-five Nm urethritis cases were confirmed by biochemical and polymerase chain reaction testing. Men with Nm urethritis were a median age of 31 years (interquartile range [IQR] = 24–38) and had a median of 2 sex partners in the last 3 months (IQR = 1–3). Nm cases were predominantly black (81%) and heterosexual (99%). Most had urethral discharge (91%), reported oral sex with a female in the last 12 months (96%), and were treated with a ceftriaxone-based regimen (95%). A minority (15%) also had urethral chlamydia coinfection. All urethral Nm isolates were nongroupable, ST-11 clonal complex (ccll), ET-15, and clustered together phylogenetically. Urethral Nm isolates were similar by fine typing (PorA P1.5–1,10–8, PorB 2–2, FetA F3-6), except 2, which had different PorB types (2-78 and 2-52). Conclusions. Between January and November 2015, 75 urethritis cases due to a distinct Nm clade occurred among primarily black, heterosexual men in Columbus, Ohio. Future urogenital Nm infection studies should focus on pathogenesis and modes of sexual transmission.